2015
DOI: 10.1128/aac.00614-15
|View full text |Cite
|
Sign up to set email alerts
|

Determination of MIC Distribution and Epidemiological Cutoff Values for Bedaquiline and Delamanid in Mycobacterium tuberculosis Using the MGIT 960 System Equipped with TB eXiST

Abstract: Because of the new mechanism of action of bedaquiline-the compound acts via inhibition of mycobacterial ATP synthase (AtpE)-it has been postulated that antimicrobial susceptibility testing (AST) is not needed in patients who have never received bedaquiline (4). However, cross-resistance between bedaquiline and the antimycobacterial drug clofazimine through overproduction of the MmpL5 efflux pump has recently been described (5, 6). Thus, resistance may develop independently of treatment with bedaquiline (2, 7).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 20 publications
4
32
1
Order By: Relevance
“…The reported MICs for bedaquiline-sensitive strains were 0.03-0.12 mg/L, considerably lower than those found in our study (Andries et al, 2005). However, Keller et al (2015) and Torrea et al (2015) reported that the MGIT 960 system equipped with EpiCenter/TB eXiST showed significantly higher MIC values than did the DAC system. The system reported bedaquiline MIC arithmetic means and medians of 0.54 mg/L and 0.4 mg/L, respectively, for the H37Rv strain.…”
Section: Resultscontrasting
confidence: 83%
“…The reported MICs for bedaquiline-sensitive strains were 0.03-0.12 mg/L, considerably lower than those found in our study (Andries et al, 2005). However, Keller et al (2015) and Torrea et al (2015) reported that the MGIT 960 system equipped with EpiCenter/TB eXiST showed significantly higher MIC values than did the DAC system. The system reported bedaquiline MIC arithmetic means and medians of 0.54 mg/L and 0.4 mg/L, respectively, for the H37Rv strain.…”
Section: Resultscontrasting
confidence: 83%
“…In addition, the bedaquiline MIC QC range using the broth microdilution method is not applicable to the widely used mycobacterial growth indicator tube (MGIT; Becton Dickinson) system (28), a commercial rapid liquid culture system for diagnosis and DST. Studies have been done to determine the mean bedaquiline MIC values (0.65 g/ml) (29) or ranges (Յ0.03 to 1.00 g/ml) (30) and epidemiological cutoffs (1.6 g/ml [29] and 1.0 g/ml [30]) for M. tuberculosis using the MGIT 960 system. However, these studies were not tier-2, multilaboratory, reproducibility studies, and in one of the studies (30), crushed tablets were used instead of pure powder.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, the MGIT960 is the gold standard. However, treatment of MDR/XDR-TB should be individualized and based on a combination of true minimum inhibitory concentration (MIC) of drugs when testing the MTB isolate in vitro and the plasma levels that can be achieved in the respective patient [17,51,52]. This may become in reach of more laboratories when cheaper MIC methods will be standardized, like the 96-well Sensititre approach [53].…”
Section: Diagnosis Of Xdr-tb; Dst/lpamentioning
confidence: 99%
“…In high-burden settings, where resources are often limited, molecular resistance assays are used instead as they have a high throughput and superior performance characteristics to conventional culture and drug-susceptibility testing [108]. However, individualized treatment is based on true minimum inhibitory concentration (MIC) of drugs when testing the MTB isolate [17,51,52]. In addition to easy-to-implement MIC testing [109], a central reference laboratory is crucial for optimal treatment outcome in XDR-TB.…”
Section: Expert Commentarymentioning
confidence: 99%